SEEKING HEALTHCARE IN PURDAH: A QUALITATIVE STUDY OF MUSLIM WOMEN IN IBADAN METROPOLIS, NIGERIA - Tunde, Fasasi Lukman; Kafayat, Aminu; Samuel, Jegede Ayodele (Gender & behaviour, 2020)
Religion is intrinsically linked to cultural values and norms that shape human behaviours. It influences people's perceptions about their health and means of seeking care to protect, sustain and improve it. Access to healthcare by Muslim women in purdah is limited by restrictions placed on their mobility. This study examined the health behaviour of women in purdah in Ibadan metropolis, Nigeria. Exploratory and qualitative techniques were adopted. Thirty (30) In-depth interviews (IDIs) for women in purdah, twenty (20) key-informant interviews (KIIs) for men, health practitioners and clerics, and four (4) Focus Group Discussions were conducted. There were restrictions in mobility of women accessing healthcare facilities, especially outside their localities, without male escorts approved by their husbands. Decisions on therapeutic choices were largely influenced by their spouses and religious doctrines. The study has implications on maternal and child health and population control programmes.